2022
DOI: 10.1111/nyas.14947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health symptoms in children and adolescents during the COVID‐19 pandemic: A meta‐analysis

Abstract: The COVID-19 pandemic and its accompanying infection control measures introduced sudden and significant disruptions to the lives of children and adolescents around the world. Given the potential for negative impacts on the mental health of youths as a result of these changes, we conducted a systematic review and meta-analysis to examine the prevalence of depressive symptoms, anxiety symptoms, and sleep disturbances in children and adolescents during the pandemic. We searched major literature databases for rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 260 publications
4
51
2
2
Order By: Relevance
“…Conversely, in a psychiatric care sample, these problems continued to increase throughout the pandemic. Our general population findings are in line with a recent meta-analysis showing a positive correlation between date of data collection and the prevalence of anxiety and depressive symptoms throughout the pandemic, with a slight downward trend since the winter semester of 2021 (Deng et al 2023). However, the pattern of mental problems over time in clinical populations are yet unclear due to limited studies in this area.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, in a psychiatric care sample, these problems continued to increase throughout the pandemic. Our general population findings are in line with a recent meta-analysis showing a positive correlation between date of data collection and the prevalence of anxiety and depressive symptoms throughout the pandemic, with a slight downward trend since the winter semester of 2021 (Deng et al 2023). However, the pattern of mental problems over time in clinical populations are yet unclear due to limited studies in this area.…”
Section: Introductionsupporting
confidence: 91%
“…In fact, within the first two months after the start of the pandemic, children reported more feelings of anxiety and depression compared to pre-pandemic time points (Luijten, van Muilekom, et al 2021; Shoshani and Kor 2022). Meta-analyses and reviews conducted over a more extended period of time have shown the persistence of these problems throughout the pandemic (Kauhanen et al 2023; Harrison et al 2022; Samji et al 2022; Deng et al 2023; Newlove-Delgado et al 2023; Ludwig-Walz et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, only three included studies reported data from 2021, with the remainder reporting outcomes from 2020. This drop-off in longitudinal data is in keeping with the findings of another meta-analysis, in which out of 162 studies that examined during-pandemic children's mental health, 135 collected data in 2020, 26 collected data in 2021, and one collected data in 2022 (Deng et al, 2023). Thus, in keeping with a recent call to action (Wade et al, 2023), studies that examine the trajectory of children's mental health outcomes beyond the first year of the pandemic year are needed to determine whether these effects have been maintained, worsened, or have resolved over time.…”
Section: Introductionsupporting
confidence: 76%
“…In their meta-analysis on sleep disturbances during the pandemic in the general population, Jahrami and colleagues found that children and adolescents represented the second most affected group after COVID-19 patients, with an overall prevalence of sleep problems of approximately 46% [ 132 ]. From another meta-analytic work, the pooled prevalence of sleep disorders among children and adolescents was 42%, with age, educational levels, and female gender correlating with depressive symptoms (pooled prevalence of 31%), which had an increase of prevalence over time [ 137 ]. Several studies from different countries reported a high prevalence of sleep disorders and poor sleep quality in adolescents during the pandemic [ 133 , 134 , 135 , 136 ].…”
Section: The Impact Of Covid-19 Outbreak On Sleep and Mental Health I...mentioning
confidence: 99%